Cadmium Stimulates the Expression of Vascular Cell Adhesion Molecule-1 (VCAM-1) via p38 Mitogen-Activated Protein Kinase (MAPK) and JNK Activation in Cerebrovascular Endothelial Cells - Sung Lyea Park; You-Mie Kim; Jin-Hee Ahn; Soo Hwan Lee; Eun Joo Baik; Chang-Hyun Moon; Yi-Sook Jung (Elsevier, 2009)
Abstract.: In this study, we examined the effect of Cd on the expression of vascular cell adhesion molecule-1 (VCAM-1) and its mechanisms in bEnd.3 cells. The treatment with Cd increased protein and mRNA expressions of VCAM-1 and increased the phosphorylations of p38, JNK, and ERK. The Cd-induced VCAM-1 expression was significantly suppressed by either a specific p38 mitogen-activated protein kinase (MAPK) inhibitor (SB202190) or a JNK inhibitor (SP600125), but not by an ERK inhibitor (U0126). These results suggest that Cd induces the expression of VCAM-1, at least in part, via p38 and JNK pathways in bEnd.3 cells. Keywords:: cadmium, vascular cell adhesion molecule-1 (VCAM-1), mitogen-activated protein kinase (MAPK)